التنسيق بين السياستين النقدية والمالية سبيل نحو كبح التضخم في الجزائر خلال الفترة 1990- 2021 - عياشي موسى; شليق عبد الجليل (جامعة الوادي University Of Eloued, 2024)
The study aims to explore the intertwined interactions between fiscal and monetary policies in Algeria and their impact on inflation during the period 1990-2021. To achieve this goal, the Autoregressive Distributed Lag Model (ARDL)was utilized. The study concluded that interest rates and exchange rates are effective in achieving inflation rates within an acceptable range. Meanwhile, the remaining variables appeared to be non-significant, indicating a weak degree of coordination between the fiscal and monetary policies in Algeria.
Coordination between monetary and fiscal policies is a means to reduce inflation in Algeria during the period from1990 - 2021
Keywords: التنسيق; السياسة المالية; السياسة النقدية; التضخم; ARDL; Coordination; fiscal policy; monetary policy; inflation; ARDLModel